Allelopathic Effects of Aqueous Extracts of Sorghum (Sorghum bicolor L. Moench) on the Early Seedling Growth of Sesame (Sesamum indicum L.) Varieties and Selected Weeds - J. C. Murimwa; J. T. Rugare; S. Mabasa; R. Mandumbu (International Journal of Agronomy)
Sesame (Sesamum indicum L.) production is lucrative to resource poor farmers in marginalised areas of Zimbabwe, although most farmers have reportedly been failing to derive maximum economic benefits from sesame production due to poor productivity. Low productivity has been attributed to several factors including challenges of weed control due to absence of registered herbicides for use in sesame in Zimbabwe. Laboratory enzyme assays were conducted using different sorghum aqueous leaf and stem extract concentrations at 0, 2.5, 5.0, 7.5, and 10.0% wv−1 to determine the effect of sorghum aqueous extracts on plant defense enzymes polyphenol oxidase (PPO), peroxidase (POD), and phenylalanine ammonia lyase (PAL) in sesame and selected weeds. Greenhouse experiments were conducted to assess the effect of sorgaab or sorgaab-Agil postemergence sprays on the seedling growth and physiology of sesame and weeds. The exposure of sesame, black jack, and goose grass to sorghum aqueous extracts caused a significant (p<0.05) concentration-dependent increase on the activity of antioxidant enzymes PAL, POD, and POD. Similarly, postemergence sprays of sole sorgaab, herbicide, and sorgaab-herbicide combination significantly (p<0.05) increased sesame and black jack seedling growth, chlorophyll content, and fluorescence but not of goose grass. From this study, it could be concluded that the allelochemicals in sorghum aqueous extracts were not effective at inhibiting the growth and physiological processes of sesame and the weeds. Therefore, resource-poor farmers cannot rely on sorgaab to control weeds in sesame but there is a need to integrate weed control options to form an effective integrated weed management program.